2010
DOI: 10.1093/europace/euq119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pacing configurations, body mass index, and position of coronary sinus lead on frequency of phrenic nerve stimulation and pacing thresholds under cardiac resynchronization therapy

Abstract: Flexible LV pacing configurations are a useful feature of CRT systems for preventing PNS. The optimal LV pacing configuration should be determined on the basis of individual patient testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 20 publications
3
54
1
1
Order By: Relevance
“…However, only onethird of patients had the Ring3 RV coil configuration available when tested. 9 In contrast to our findings, Burri et al 8 reported that Ring3 RV coil configuration had a higher LV voltage threshold at 0.4 -0.5 ms when compared with Tip3 RV coil and Tip3 Ring configurations, without a difference between Tip3 RV coil and Tip3 Ring configurations. However, this study had 2 limitations: (1) Ring3 RV coil was programmed only 3% of the time, and (2) testing was not performed for these 3 configurations in each patient.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…However, only onethird of patients had the Ring3 RV coil configuration available when tested. 9 In contrast to our findings, Burri et al 8 reported that Ring3 RV coil configuration had a higher LV voltage threshold at 0.4 -0.5 ms when compared with Tip3 RV coil and Tip3 Ring configurations, without a difference between Tip3 RV coil and Tip3 Ring configurations. However, this study had 2 limitations: (1) Ring3 RV coil was programmed only 3% of the time, and (2) testing was not performed for these 3 configurations in each patient.…”
contrasting
confidence: 99%
“…8,9 Similar to our findings, a study comparing these 3 configurations in 96 patients reported that Tip3 RV coil had a significantly lower voltage threshold at 1 ms when compared with Tip3 Ring configuration. However, only onethird of patients had the Ring3 RV coil configuration available when tested.…”
Section: Prior Studies Comparing LV Pacing Configurationssupporting
confidence: 88%
“…PNS needs to be managed at the same pacing sites that are deemed optimal for CRT. 6,7,9,11 When PNS is detected at implantation, several approaches are used: moving the lead to a different position in the vein, programming the LV cathode to a different electrode in devices featuring this technology, or lowering the LV output to avoid PNS when the other options have failed. 6,11,14 LV lead repositioning to another vein is the last resort and is possible only when other coronary veins are suitable for LV lead placement.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Phrenic nerve stimulation (PNS) is a major complication that may result in withdrawal of CRT. PNS is observed in 33% to 37% of patients, [6][7][8] and although it is actively addressed in different ways during implantation, 6 it may be difficult to overcome in the long-term management of CRT patients. [9][10][11] Indeed, ≈15% of patients need to be reevaluated after hospital discharge because of PNS occurrence at follow-up, [9][10][11] and ≈6.6% eventually report PNS symptoms at long-term followup, despite multiple attempts to avoid PNS.…”
mentioning
confidence: 99%
“…[6][7][8] An important limiting factor in the implementation of successful CRT are often the variations and limitations of the anatomy of the coronary veins and the position of the cardiac veins relative to the phrenic nerve. 5,[9][10][11][12][13][14] Lead movement after implantation and phrenic nerve stimulation (PNS) due to patient posture are challenges that we face. In fact, a 12% rate of CRT failure postoperatively related to either loss of LV capture or PNS has been reported.…”
Section: Introductionmentioning
confidence: 99%